A proposed role for neutrophil extracellular traps in cancer immunoediting - Berger-Achituv, Sivan; Brinkmann, Volker; Abu-Abed, Ulrike; Kühn, Lars I.; Ben-Ezra, Jonathan; Elhasid, Ronit; Zychlinsky, Arturo (Frontiers in Immunology, 2013)
Upon activation, neutrophils release fibers composed of chromatin and neutrophil proteins termed neutrophil extracellular traps (NETs). NETs trap and kill microbes, activate dendritic cells and T-cells, and are implicated in auto-immune and vascular diseases. Given the growing interest in the role of neutrophils in cancer immunoediting and the diverse function of NETs, we searched for NETs release by tumor associated neutrophils (TANs). Using pediatric Ewing sarcoma (ES) as a model, we retrospectively examined histopathological material from diagnostic biopsies of 8 patients (mean ± SD age of 11.5 ± 4.7 years). TANs were found in 6 patients and in 2 of those we identified NETs. These 2 patients presented with metastatic disease and despite entering complete remission after intensive chemotherapy had an early relapse. NETs were not identified in the diagnostic biopsies of 2 patients with localized disease and 2 with metastatic disease. This study is the first to show that TANs in ES are activated to make NETs, pointing to a possible role of NETs in cancer.